Pathogenetic and Therapeutic Applications of Tumor Necrosis Factor-α (TNF-α) in Major Depressive Disorder: A Systematic Review - Ma, Ke (Int J Mol Sci, 2016)
Major depressive disorder (MDD) is characterized by mood, vegetative, cognitive, and even psychotic symptoms and signs that can cause substantial impairments in quality of life and functioning. Up to now, the exact pathogenesis of MDD remains poorly understood. Recent research has begun to reveal that the pro-inflammatory cytokines, particularly, tumor necrosis factor-α (TNF-α), play an integral role in the pathophysiology of depressive disorders and the mechanism of antidepressant treatment. On the base of several observations: it is found that subsets of MDD patients have enhanced plasma levels TNF-α; antidepressant treatments had linked with the decline of TNF-α; central administration of TNF-α gives rise to sickness behavior which shares features with depression; and a blockade of it can ameliorate depressive symptomatology in animal models and clinical trials. In this review article, we focus on recent evidence linking TNF-α and MDD looking at data from animal and clinical studies, illustrating the pathophysiological role, susceptibility and its therapeutic application in depression. We conclude by discussing future directions for research, in particular the opportunities for the development of novel therapeutics that target TNF-α. This will be very important for designing preventative strategies and for the identification of new drug targets and preventative strategies.